1985
DOI: 10.1007/bf00291979
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the stimulation of insulin release in vitro by HB 699, a benzoic acid derivative similar to the non-sulphonylurea moiety of glibenclamide

Abstract: HB 699 is a benzoic acid derivative similar to the non-sulphonylurea moiety of glibenclamide. The mechanisms whereby it affects B-cell function have been studied in vitro with mouse islets. In the presence of 3 mmol/l glucose, HB 699 decreased 86Rb+ efflux and accelerated 45Ca2+ efflux from islet cells, depolarized the B-cell membrane and induced an electrical activity similar to that triggered by stimulatory concentrations of glucose, and increased insulin release. The changes in 45Ca2+ efflux and insulin rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 28 publications
5
36
0
Order By: Relevance
“…The paradoxical acceleration of 86Rb efflux that the drug produced under these conditions was not unexpected and does not necessarily contradict the above interpretation. It is seen whenever a substance augments Ca24 influx and depolarization in P-cells, whose membrane is already depolarized by a decrease in K4 permeability (Henquin, 1980;Henquin & Meissner, 1982;Matthews & Shotton, 1984 a,b;Garrino et al, 1985;. Usually, however, this increase in 'Rb efflux is abolished by omission ofextracellular Ca2" and not only attenuated as observed here with 1 -adamantanamine.…”
Section: Effects Ofvarious Adamantane Derivativessupporting
confidence: 48%
See 2 more Smart Citations
“…The paradoxical acceleration of 86Rb efflux that the drug produced under these conditions was not unexpected and does not necessarily contradict the above interpretation. It is seen whenever a substance augments Ca24 influx and depolarization in P-cells, whose membrane is already depolarized by a decrease in K4 permeability (Henquin, 1980;Henquin & Meissner, 1982;Matthews & Shotton, 1984 a,b;Garrino et al, 1985;. Usually, however, this increase in 'Rb efflux is abolished by omission ofextracellular Ca2" and not only attenuated as observed here with 1 -adamantanamine.…”
Section: Effects Ofvarious Adamantane Derivativessupporting
confidence: 48%
“…The same sequence of events is also believed to underlie the effects of sulphonylureas of the first and second generation (Henquin, 1980;Henquin & Meissner, 1982;Matthews & Shotton, 1984a;Ferrer et al, 1984) and of benzoic acid derivatives of the sulphonylureas of second generation (Garrino et al, 1985;. In contrast to all these agents, 1-adamantanamine may also affect intracellular Ca2" stores without this effect being sufficient to trigger release.…”
Section: Effects Ofvarious Adamantane Derivativesmentioning
confidence: 94%
See 1 more Smart Citation
“…The compound HB699, which is similar to the non-sulphonylurea moiety of glibenclamide, was shown to be slightly less effective than glibenclamide itself but much more potent than tolbutamide. Garrino et al (1985) demonstrated that HB699 depolarized B-cells by decreasing K+ permeability and induced insulin release. They found that HB699 was much less potent than glibenclamide and only slightly more potent than tolbutamide.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Garrino et al (1985) found that 1O-7IM glibenclamide reduced 86Rb efflux and increased insulin release from mouse islets perifused with a medium containing 3 mm glucose, although no attempt was made in that study to establish a threshold concentration for the sulphonylurea. Commonly, authors have tended to use higher concentrations of glibenclamide in their studies.…”
Section: Conscious Rat Studiesmentioning
confidence: 99%